Performance Evaluation of the GPM Satellite Rainfall in the Wampu Basin, North Sumatera, Indonesia - Hakim, Anita Maulidiyah Rahma; Harisuseno, Donny; Sisinggih, Dian; Asmaranto, Runi (Fakultas Teknik, Universitas Brawijaya, 2025)
Rainfall data is crucial in water resources management, particularly associated with its quantity, quality, and spatial and temporal availability in a basin. This study aims to assess the feasibility of Global Precipitation Measurement (GPM) satellite rainfall data to represent rainfall in the Wampu basin. The observed and the GPM rainfall data were collected for 2001 – 2022. Rainfall data from observations and satellites are classified into seven rainfall depth classes with an interval of 10 mm for each class. The GPM was calibrated by determining each class’s correction factor (CF). Calibration is carried out by adjusting the CF value until the difference between the probability of occurrence of satellite and observation data for 2001 – 2017 shows a minimum value. The accuracy of the yielded CF was then validated by evaluating the estimated rainfall from the GPM with the observed rainfall for 2018 – 2022. The results show that the CF of GPM varies from 0.9 – 1.012 for rainfall intervals 0 – 10 mm, 10 – 20 mm, 20 – 40 mm, 40 – 50 mm, 50 – 100 mm, 100 – 110 mm, and >110 mm, respectively. Then, the validation results show an “Excellent” level of accuracy between the corrected GPM and the observed data.